Virome of red sea brine pools and other hydrothermal vents - Aziz, Sherry Kamal Berty (AUC Knowledge Fountain, 2017)
The central rift of the Red Sea has 25 brine pools that vary in their physical and geochemical characteristics, three of which, Atlantis II (ATIID), Discovery Deep (DD) and Kebrit Deep (KD), have high salinity, temperature and metal content. Previous studies reported bacterial and archaeal inhabitants in these brine pools, but few studies addressed the viral communities. Therefore, sediment cores and water samples were collected from ATIID, DD, KD brine pools in addition to a neighboring two brine-influenced sites. Shotgun DNA pyrosequencing was performed to all samples. Sediment-specific reads were generated and annotated. The phylogenetic and biochemical uniqueness of the deepest ATIID brine pool sediments was clearly reported with unique viral signature for the deepest two layers. Bacteria dominate the deepest ATIID sediments sections whereas viruses are more prevalent in other sediment sections. Water samples were also collected and analyzed for their viral community. Water and sediment samples were analyzed using different approaches. The traditional method of analysis was used in addition to another approach called Genome relative Abundance and Average Size (GAAS) approach which showed that there is an enormous data that was overlooked using the classical method. GAAS estimates both viral abundance and the average genome size for each section to overcome the disadvantage of sampling bias during viral analysis. Different sections showed different viral communities and different average genome sizes based on different stressors. Shannon diversity index, richness and evenness were calculated for each section to obtain accurate estimates of viral inhabitants. Our results showed that there is direct relationship between viral diversity and average genome sizes. Interestingly, prophages and gene transfer agents (GTAs) were also identified in the analysis of the Red Sea brine pools such as Rhodobacter phage. It was linked to horizontal gene transfer, viral diversity and evolution. Other hydrothermal vents were also analyzed for their viral communities and compared to the Red Sea brine pools. The highest Shannon diversity index was estimated in the Red Sea hydrothermal vent which renders the Red Sea environments more unique and distinct from other hydrothermal vents.